Why Preparing An Emergency Fund Is Matter To Young Adults? - Kamarudin, Nur Shuhada; Ramli, Nur Ainna; Rasedee, Ahmad Fadly Nurullah (International Journal of Engineering and Technology, 2018)
Up to now, far too little attention has been paid to emergency fund preparation among young adults. This study provides an exciting opportunity to advance our understanding of why young adults prepare their emergency fund and what their perspective on that. Open-ended survey was used to answer the research objective. Interestingly, the purpose of emergency fund allocation among young in this study was not only to cover their necessity unexpected expenses and medical bills, but to help them to travel and paid for their leisure activities. Successful in preparing for emergency fund was found related to wise money management plan. The present study provides additional evidence with respect to study emergency fund from a behavioural perspective.